Aerobic mineralization of vinyl chloride by a bacterium of the order Actinomycetales. - Phelps, T J (1991)
A gram-positive branched bacterium isolated from a trichloroethylene-degrading consortium mineralized vinyl chloride in growing cultures and cell suspensions. Greater than 67% of the [1,2-14C]vinyl chloride was mineralized to carbon dioxide, with approximately 10% of the radioactivity appearing in cell biomass and another 10% appearing in 14C-aqueous-phase products.